Software Quality: A mosaic of abstractions (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2012)
Today software market is highly volatile and competitive. The complexity of commercial software is on the rise along with the time constraint to produce high quality software. Increased software complexity probably leads to more and more defects but still organizations can afford it at the cost of being initiators. The idea of this paper is to nuance and provide an overview of the landscape of what sometimes briefly (and mostly thoughtlessly) simply is labeled quality. Quality can be a very elusive concept that can be approached from a number of perspective dependent on once take and interest. Every organization is unique and has its own needs so it is difficult to recommend â€œone size fit allâ€ solution.